Filling the ecological data gap: A detailed habitat study of the neglected bleeding toad (Leptophryne cruentata) - RIZKI KURNIA TOHIR; MIRZA DIKARI KUSRINI; ANI MARDIASTUTI; BOBY DARMAWAN; DEDE AULIA RAHMAN (Society for Indonesian Biodiversity, 2025)
Abstract. Tohir RK, Kusrini MD, Mardiastuti A, Darmawan B, Rahman DA. 2025. Filling the ecological data gap: A detailed habitat study of the neglected bleeding toad (Leptophryne cruentata). Biodiversitas 26: 3973-3984. Effective conservation of threatened amphibians requires detailed ecological knowledge, yet many species remain poorly studied. This research focuses on the bleeding toad (Leptophryne cruentata), a Critically Endangered and legally protected endemic amphibian in Java, Indonesia. Despite its conservation status, ecological information about the species is scarce. We conducted habitat survey across 11 sites within Gunung Gede Pangrango National Park, West Java, from March 2023 to February 2024. A 150 m transect was randomly placed in previously known microhabitats, with environmental variables recorded twice daily and nightly (07:00-09:00) to assess diel habitat variation. We assessed elevational distribution, microclimatic parameters, hydromorphological variables, and aquatic microhabitat types. The species was observed between 1,281 and 1,892 m asl, with additional records extending to 2,089 m asl. Significant diurnal variations in air and water temperatures were found. Daytime air temperatures ranged from 15.7-21.8°C and water temperatures from 15.6-22.3°C, both significantly higher than nighttime values (p<0.001). Humidity remained consistently high (75-100%) with minimal diurnal variation. Bleeding toad was associated with moderately to highly shaded habitats and diverse aquatic environments, including waterfalls, streams, swamps, and headwall seeps. A novel observation was its presence in a terrestrial habitat 260 m from the nearest stream. These findings indicate ecological plasticity and highlight critical habitat parameters essential for conservation planning. Understanding the species’ elevational limits, microhabitat use, and environmental sensitivity provides a valuable foundation for habitat management, reintroduction strategies, and climate resilience planning for this imperiled montane amphibian.